Judging the Inner Judge: On the Genesis of Kant's Theodicy Essay - Muchnik, Pablo (Con-Textos Kantianos. International Journal of Philosophy, 2026)
This paper interprets Kant’s 1791 essay, “On the Miscarriage of All Philosophical Trials in Theodicy,” as an exercise in philosophical self-examination. Instead of attributing the rejection of doctrinal theodicy to the maturation of his moral theory or the impact of external influences, I read Miscarriage as Kant’s belated attempt to restrain his own rationalist tendencies even after writing the Critique of Pure Reason. Those tendencies emerge throughout the 1780s in his lectures on religion and writings on history. Kant repudiates them in Miscarriage, recasting the figure of Job as a model of “authentic theodicy,” a man who renounces knowledge claims about God in favor of his moral integrity. This move upends Kant’s earlier theodicean strategies and curbs the temptation that led him to embrace them. So construed, Kant’s 1791 essay can be read as a tribunal in which he judges his prior rationalist self –a philosophical autobiography of sorts.